Supplementation with selenium and coenzyme Q10 in an elderly Swedish population low in selenium — positive effects on thyroid hormones, cardiovascular mortality, and quality of life - Alehagen, Urban; Alexander, Jan; Aaseth, Jan O.; Larsson, Anders; Opstad, Trine B. (BMC medicine, 2024)
Background Selenium-dependent deiodinases play a central role in thyroid hormone regulation and metabolism. In many European countries, insufficient selenium intake may consequently lead to adverse effects on thyroid function. In this randomised placebo-controlled double-blind study, we examined the effect of supplementation with selenium and coenzyme Q 10 on thyroid hormonal status, cardiovascular (CV) mortality and health-related quality of life (Hr-QoL). Methods Free T3, free T4, reverse T3, and TSH were determined in 414 individuals at baseline, and the effect of selenium yeast (200 µg/day) and coenzyme Q 10 (200 mg/day) supplementation on hormone concentrations, CV mortality and Hr-QoL was evaluated after 48 months using Short Form 36 (SF-36). Pre-intervention plasma selenium was low, mean 67 µg/L, corresponding to an estimated intake of 35 µg/day. Changes in concentrations of thyroid hormones following the intervention were assessed using T -tests, repeated measures of variance, and ANCOVA analyses. Results In the total population, the group with the lowest selenium concentration at baseline presented with significantly higher levels of TSH and lower levels of fT3 as compared to subjects with the highest selenium concentration. Supplementation with selenium and coenzyme Q 10 for 4 years significantly increased fT3 and rT3, decreased fT4, and diminished the increase in TSH levels compared with placebo treatment ( p = 0.03, all). In the placebo group, TSH and fT4 values above the median were associated with an increase in 10-year CV mortality, as compared with the mortality rate among those with TSH and fT4 below the median ( p < 0.04, both), with no difference in mortality rate according to TSH and fT4 levels in the active intervention group. Similarly, TSH > median and fT3 < median were associated with a decline in mental Hr-QoL measures vs. TSH < and fT3 > median in the placebo group during 4 years of follow-up, but this was wiped out in the active group. Conclusions Supplementation with selenium and coenzyme Q 10 had a beneficial effect on thyroid hormones with respect to CV mortality and Hr-QoL outcomes. The initial deficient selenium status was associated with an impaired thyroid function and the changes in thyroid hormone levels can be explained by increased activity of deiodinases. We conclude that a substantial part of the elderly study population might suffer from suboptimal thyroidal function with adverse clinical implications due to selenium deficiency. Trial registration This study was registered at ClinicalTrials.gov and has the identifier NCT01443780. Since it was not mandatory to register at the time the study began, the study has been registered retrospectively.